2020
DOI: 10.1111/btp.12747
|View full text |Cite
|
Sign up to set email alerts
|

Tree communities and soil properties influence fungal community assembly in neotropical forests

Abstract: The influence exerted by tree communities, topography, and soil chemistry on the assembly of macrofungal communities remains poorly understood, especially in highly diverse tropical forests. Here, we used a large dataset that combines inventories of macrofungal Basidiomycetes fruiting bodies, tree species composition, and measurements for 16 soil physicochemical parameters, collected in 34 plots located in four sites of lowland rain forests in French Guiana. Plots were established on three different topographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 85 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Yang et al (2012) also indicated that abundant rainfall and high temperatures are important factors for macrofungal productivity. Although many environmental factors were discussed in this study and other similar work on the topic, the inclusion of below‐ground factors, such as soil properties (Schimann et al 2020), and the temperature and moisture levels of the soil (Pinna et al 2010), should also be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al (2012) also indicated that abundant rainfall and high temperatures are important factors for macrofungal productivity. Although many environmental factors were discussed in this study and other similar work on the topic, the inclusion of below‐ground factors, such as soil properties (Schimann et al 2020), and the temperature and moisture levels of the soil (Pinna et al 2010), should also be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…A key objective in studying the ecological processes behind macrofungal community formation is to better understand which factors shape the distribution patterns of macrofungal communities (Martiny et al 2006). Previous research has reported that both biotic and abiotic elements influence macrofungal diversity and distribution, including geographical, climatic, soil and floristic cover (O'Dell et al 2000; Gassibe et al 2015; Bakray et al 2020; Schimann et al 2020). Among these factors, plant community structures have been suggested to be more strikingly correlated with the diversity and structure of fungal communities (Peay et al 2013; Mueller et al 2014; Chen et al 2017; Bittebiere et al 2020; Francioli et al 2020; Pecoraro et al 2020).…”
Section: Introductionmentioning
confidence: 99%